محبت ایک بیانیہ مقبول عام ناول کے تناظر میں - Razia Batool Jafri; Dr. Aqeela Javeed (Khayaban - خیابان, 2022)
'Love at any cost' is the narrative upon which the edifice of the contemporary novel is constructed. Be it either romantic, social, historical or espionage in nature, theme of love is an integral component of all kinds of writing. There is no doubt that some worthy men of letters have expounded theme of love as a highly esteemed moral value. But in contemporary popular fiction, this depiction of love has created an allusion of false hopes and day dreaming in the minds of the readers. The present day novelists like Zafar Umar, A. R. Khatoon, Bushra Rehman, Razia Butt, Abdul Haleem Sharar, Naseem Hijazi, M. Aslam, M. A. Rahat, Muhayyudin Nawab, Umera Ahmad, Riffat Siraaj and Namra Ahmad have presented theme of love in a typical way devoid of any creativity. If their concept of love is perused critically, a monotonous frame of construction appears to be followed by all writers. From the beginning of falling in love to the end of getting married, vanquishing all the obstacles in the way, love is always presented triumphant at the denouement. This sort of narrative has misdirected the expectations of the ordinary readers of middle class having an average intellect and education. Thus, the sociologist, who are examining the reasons for the increase in the elopement cases at an early age should also consider this narrative of celebrated genre as a major factor behind the deterioration of our domesticity .